The Effect of Propolis Addition on Feed to Increase the Immune Non- Specific Response in Pangasius hypophthalmus - Ahmad Sabri; Iesje Lukistyowati; Morina Riauwaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in April until June 2018 at the Experimental Pond and Laboratory of Parasites and Fish Diseases, Faculty of Fisheries and Marine, University of Riau. The purpose of this study was to determine the effect of the addition of propolis on feed to improve the non-specific immune response of Pangasius hypophthalmus which is maintained in cages. The research method used in this study was an experimental method with a completely randomized design (CRD) consisting of 5 treatments and 3 replications, with the treatment of feeding containing propolis ie P0 (without the addition of propolis), P1 (addition of propolis600 ppm / kg of feed ), P2 (addition of propolis 700 ppm / kg of feed), P3 (addition of propolis 800 ppm / kg of feed) and P4 (addition of propolis 900 ppm / kg of feed). The test fish used was jambal siam fish with a size of 8-10 cm as many as600 tails. The parameters measured are; total leukocytes, leukocyte differentiation, phagocytic activity, survival, absolute weight growth and water quality measurements. The results obtained from the study, namely there is the effect of giving propolis in feed with the best dose is 800 ppm / kg of feed (addition of propolis 800 ppm / kg feed) is real P <0.05 and the best dose with a total leukocyte of 10.06 x104 cells / mm3, lymphocyte percentage 84.00%, neutrophils 6.33%, monocytes 9.67%, phagocytic activity 35.33%, survival 98% and absolute weight growth 39.18 g. Keywords: Leukocytes, Pangasius hypophthalmus, Propolis